2017
DOI: 10.1007/s00330-017-5050-2
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between benign and malignant breast lesions using volumetric quantitative dynamic contrast-enhanced MR imaging

Abstract: • qDCE-MRI parameters are useful for discriminating between malignant and benign breast lesions. • K , K and MaxSlope were independent predictors of breast malignancy. • qDCE-MRI has a better diagnostic ability than morphology and kinetic analysis. • qDCE-MRI can be used to improve the diagnostic accuracy of breast malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
2
14
1
Order By: Relevance
“…At a lower field strength, one has to compromise on using either a high temporal resolution suitable for PK analysis or a high spatial resolution for detailed morphologic assessment. Our findings are in good agreement with prior studies at 1.5 and 3T, which demonstrated the potential of PK parameters to aid in the differentiation of benign from malignant tumors [14,18,32,[44][45][46][47]. We integrated the information from quantitative PK analysis to established reporting guidelines, i.e., BI-RADS, showing that PK-enhanced BI-RADS improved diagnostic accuracy from 88.4% to 97.7% by reducing false-positive findings.…”
Section: Discussionsupporting
confidence: 88%
“…At a lower field strength, one has to compromise on using either a high temporal resolution suitable for PK analysis or a high spatial resolution for detailed morphologic assessment. Our findings are in good agreement with prior studies at 1.5 and 3T, which demonstrated the potential of PK parameters to aid in the differentiation of benign from malignant tumors [14,18,32,[44][45][46][47]. We integrated the information from quantitative PK analysis to established reporting guidelines, i.e., BI-RADS, showing that PK-enhanced BI-RADS improved diagnostic accuracy from 88.4% to 97.7% by reducing false-positive findings.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, the MRI protocol itself can also have influence on our results 55 . We aimed to control for this bias and adopted our imaging protocol to international standards and used well established criteria to assess the tumor vascularization 16,18,28,29,45,56 . Future studies should investigate the repeatability of our results with different software, MRI protocols and identify the potential impact of the reader on our results.…”
Section: Discussionmentioning
confidence: 99%
“…When employed in the very early phase (0-60 s after contrast injection), it can generate kinetic parameters reflecting contrast agent inflow effects. The diagnostic utility of these generated parameters in differentiating malignant from benign lesions and in improving positive predictive value has been proven in recent years [5][6][7][8][9][10][11][12][13][14][15]. Moreover, several studies have shown that these parameters present higher or comparable accuracy to Breast Imaging Reporting and Data System (BI-RADS) [1] delayed phase kinetic curve assessment, suggesting that ultrafast DCE-MRI in the very early phase may substitute for the standard DCE-MRI delayed phase [5,7,9,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%